Multisample Data Acquisition System for Resistance Measurement of High-temperature Superconductors - Yahya, Ahmad Kamal; Md Salleh, Faizah (Universiti Putra Malaysia Press, 1999)
The construction of a system for simultaneous multiple sample resistance measurement of high-temperature superconductors is reported. The data acquisition system uses the PCLD785B relay board controlled by parallel input-output 8255A PIA emulation through a PCL724B card to perform multisample measurements by signal switching. The system, which is controlled by a 80486 microcomputer, is able to log, store and plot temperature and resistance readings and can be modified to accommodate up to six samples per run. The temperature can be measured with a precision of 0.1 K and accuracy of ±1 K. The absolute-zero offset value is less than 0.1 K. The maximum switching voltage, maximum current and open channel isolation resistance are 125 V, 2 A and 100 MQ, respectively. The closed channel